Effects of a quercetin-rich onion skin extract on 24 h ambulatory blood pressure and endothelial function in overweight-to-obese patients with (pre-)hypertension: a randomised double-blinded placebo-controlled cross-over trial - Verena Brüll; Constanze Burak; Birgit Stoffel‐Wagner; Siegfried Wolffram; Georg Nickenig; Cornelius Müller; Peter Langguth; Birgit Alteheld; Rolf Fimmers; Stefanie Naaf; Benno F. Zimmermann; Peter Stehle; et al. (2015)
The polyphenol quercetin may prevent CVD due to its antihypertensive and vasorelaxant properties. We investigated the effects of quercetin after regular intake on blood pressure (BP) in overweight-to-obese patients with pre-hypertension and stage I hypertension. In addition, the potential mechanisms responsible for the hypothesised effect of quercetin on BP were explored. Subjects (n 70) were randomised to receive 162 mg/d quercetin from onion skin extract powder or placebo in a double-blinded, placebo-controlled cross-over trial with 6-week treatment periods separated by a 6-week washout period. Before and after the intervention, ambulatory blood pressure (ABP) and office BP were measured; urine and blood samples were collected; and endothelial function was measured by EndoPAT technology. In the total group, quercetin did not significantly affect 24 h ABP parameters and office BP. In the subgroup of hypertensives, quercetin decreased 24 h systolic BP by -3·6 mmHg (P=0·022) when compared with placebo (mean treatment difference, -3·9 mmHg; P=0·049). In addition, quercetin significantly decreased day-time and night-time systolic BP in hypertensives, but without a significant effect in inter-group comparison. In the total group and also in the subgroup of hypertensives, vasoactive biomarkers including endothelin-1, soluble endothelial-derived adhesion molecules, asymmetric dimethylarginine, angiotensin-converting enzyme activity, endothelial function, parameters of oxidation, inflammation, lipid and glucose metabolism were not affected by quercetin. In conclusion, supplementation with 162 mg/d quercetin from onion skin extract lowers ABP in patients with hypertension, suggesting a cardioprotective effect of quercetin. The mechanisms responsible for the BP-lowering effect remain unclear.